THE MAIN MEANS AND FORMS OF CHILDREN'S HEALTH PROMOTION ACTIVITIES IN EDUCATIONAL INSTITUTIONS - Abdilaxatov Zafar Abdigapirovich (Web of Journals Publishing, 2025)
The article examines the primary means and organizational forms used to promote children's health within educational institutions. It discusses the integration of health-promoting programs into the school curriculum, the implementation of physical education, hygiene education, psychological support, and the creation of a safe and supportive learning environment. The role of educators, school healthcare personnel, and collaboration with parents is also emphasized as crucial to fostering a culture of health and well-being among students.
Keywords: Children’s health, health promotion, educational institutions, school programs, physical activity, hygiene education, psychological support, school environment, student well-being, health education.